Distribution of the African rice gall midge, Orseolia oryzivora Harris and Gagne and its parasitoids in Nigeria - Ukwungwu, M.N.; Joshi, R.C. (Informa UK Limited, 1992)
The African rice gall midge, Orseolia oryzivora Harris and Gagné has become one of the major biotic constraints to rice production in Nigeria. A survey of gall midge distribution in Nigeria showed that the pest was common in the savannah and forest zones on rice grown under lowland ecologies. Endemic areas were identified which could serve as ‘hot spots' for varietal screening. Indigenous parasitoids of the pest were identified as: Platygaster diplosisae Risbec, Aprostocetus pachydiplosisae Risbec and Aphanogmus spp. The dominant parasitoid was, however, P. diplosisae.